Features of direct implantation in chronic foci of odontogenic infection - Gudaryan А.А.; Drobyazgo M.G.; Shamrai A.N. (Medičnì Perspektivi)
The article presents the results of the developed therapeutic and prophylactic complex and efficacy of immediate implantation in 66 patients with chronic foci of odontogenic infection in the periapical region. Objective: to increase preventive measures of inflammatory and infectious complications and optimization of osteo-integrative processes in immediate implantation after tooth extraction, with periapical foci of chronic infection. It was found that the use of the developed medical complex of following up direct implantation includes the use of local photodynamic therapy, platelet, rich in fibrin as a injection and membranes; this allowed to create a favorable background for the prevention of inflammatory and infectious complications in the peri-implant area and created a favorable background for the osseo-integration of implants in 97.1% of the investigated.